2018
DOI: 10.1039/c8fo00148k
|View full text |Cite
|
Sign up to set email alerts
|

Networks of micronized fat crystals grown under static conditions

Abstract: Dispersing micronized fat crystals (MFCs) in oil is a novel route to largely decouple fat crystallisation and network formation and thus to simplify the manufacture of fat-continuous food products. MFCs dispersed in oil form a weak-interaction network organized by crystal aggregates in a continuous net of crystalline nanoplatelets. The rough surface of MFC nanoplatelets hampers stacking into one-dimensional aggregates, which explains the high mass fractal dimensions of the networks formed in MFC dispersions. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 56 publications
(104 reference statements)
4
49
0
Order By: Relevance
“…The additional crystals observed after 2 days connected individual crystal clusters into a larger fat crystal network. This observation is in accordance with the weak-link network of fractal fat crystal networks as shown by Martens et al [32] and Nikolaeva et al [32,33] Indeed, De Graef [34] observed a comparable morphological evolution during static crystallization and subsequent isothermal crystallization for palm oil. Using CLSM with a higher resolution, very thin filamentous crystal structures grew outwards from the clusters, like a corona, connecting and embedding the larger crystal clusters in a continuous fat crystal network.…”
Section: Microstructural Evaluationsupporting
confidence: 88%
“…The additional crystals observed after 2 days connected individual crystal clusters into a larger fat crystal network. This observation is in accordance with the weak-link network of fractal fat crystal networks as shown by Martens et al [32] and Nikolaeva et al [32,33] Indeed, De Graef [34] observed a comparable morphological evolution during static crystallization and subsequent isothermal crystallization for palm oil. Using CLSM with a higher resolution, very thin filamentous crystal structures grew outwards from the clusters, like a corona, connecting and embedding the larger crystal clusters in a continuous fat crystal network.…”
Section: Microstructural Evaluationsupporting
confidence: 88%
“…[1] Recent developments in the combination of rheology with molecular spectroscopy and/or imaging techniques have boosted our molecular-level understanding of nonconfined flow, in relation with shear-induced microstructural rearrangements, even in complex fluids. For instance, rheo-magnetic resonance imaging (rheo-MRI) [2] enables detecting shear-induced structural changes, such as alignment [3] or network destruction or rejuvenation, [4] that occur at micrometer/millimeter scales, whereas rheo-small-angle X-ray diffraction (rheo-SAXD) offers insight into changes, for example, in terms of the sizes of the structural elements, that occur at a submicron scale. [4,5] However, as has been demonstrated for emulsions [6] and granular media, [7] strongly confined flow properties cannot be inferred from measurements carried out in nonconfined conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In order to assess the impact of industrial processing conditions on CTDs, measurements were performed on two margarines with identical fat composition but manufactured by either the conventional votator process, or by direct emulsification in a micronized fat crystal (MFC) dispersion . In comparison with the votator process, the MFC process allows manufacturing of stable emulsions with a smaller amount saturated fat.…”
Section: Resultsmentioning
confidence: 99%
“…One fat spread was prepared using the conventional votator process, where water and a molten fat blend are rapidly cooled in a scraped surface heat‐exchanger . Another spread was prepared by dispersing water in a slurry of micronized fat crystals (MFC) in oil . The fat blend composition and the total fat level in both spreads were identical.…”
Section: Methodsmentioning
confidence: 99%